The halo effect of PDO labeling on sensory experience and consumer perception of Bergkäse - Hannah Innerbichler; Florian Danzl; Jürgen König; Katrin E. Bach (Applied Food Research)
The Protected Designation of Origin (PDO) label is awarded to foods exclusively produced within a designated area. Austria has eleven registered PDO foods, seven of which are cheeses, including the hard raw milk cheese Tiroler Bergkäse PDO. Some manufacturers in Tyrol produce their cheeses according to the PDO specification but hesitate to commercialize them as such. However, foods bearing a seal (PDO, organic, fair trade) can be perceived as possessing superior taste, quality, and health benefits, and can influence consumers’ willingness-to-pay. This study examines the effect of PDO labeling on the sensory experience, the purchase criteria for cheese, overall liking, perceived quality, perceived healthiness, purchase intention, and willingness-to-pay of Bergkäse, a hard raw milk cheese. In a one-way (PDO label vs. control) between-groups experiment, 165 participants tasted the same cheese and completed a questionnaire, with only the informational text differing between groups. Results show that many taste descriptors (e.g. high-quality flavor), overall liking, perceived quality, the purchase criterion quality labels (AMA, PDO etc.), and purchase intention were rated significantly higher in the PDO group. This suggests a halo effect, where a positive impression of one attribute favorably influences the consumer's overall opinion. In this study, the PDO label did not affect the willingness-to-pay. The effects of the tested moderators were almost entirely absent. This research implies that Tyrolean cheese manufacturers producing Bergkäse according to the PDO specification may consider retailing their products with the PDO label to enhance the taste experience, perception, and purchase intention of consumers.